The Dynamics of Implementing Religious Development Programs in Secondary Schools in the Digital Era - Risa Alawiyah; Syahidin; Agus Fakhruddin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the dynamics of the implementation of religious guidance programs in secondary schools in the digital era. The study used a descriptive qualitative approach with a case study type conducted in three types of schools: SMA, SMK, and MAN. Data collection techniques were carried out through observation, interviews, and documentation, involving principals, teachers, and students involved in religious activities. The results of the study indicate that the religious guidance program is implemented in a structured and sustainable manner through daily, weekly, and annual activities, such as Quranic recitation, congregational prayers, religious lectures, infaq activities, and commemorations of Islamic holidays. Each type of school has different characteristics, with SMA and SMK tending to emphasize the habituation of religious activities, while MAN shows a stronger integration between learning and worship practices. However, program implementation faces various dynamics in the digital era, such as the use of devices that disrupt concentration, limited teacher supervision, a lack of activity variety, and the influence of the social environment. On the other hand, the use of digital technology in religious activities is still not optimal and tends not to be systematically integrated. The level of student involvement also shows variation, ranging from active as drivers of activities to passive as participants. Thus, the development of innovative, adaptive, and participatory strategies is necessary, such as utilizing interactive digital media in religious activities, involving students as program drivers through religious organizations, and developing more varied activities based on the needs of the digital generation. These strategies are expected to increase student engagement and strengthen the internalization of religious values ​​in daily life.